Keputusan Pembelian Produk MS Glow Skincare Ditinjau dari Celebrity Endorser, Citra Merek, dan Kepercayaan Konsumen: Studi pada Pengguna Produk MS Glow Skincare Store di Sukoharjo - Yuliyanti Setyaningsih; Sri Hartono; Ibnu Suryo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study will test and assess the relationship between consumer trust, brand image, and celebrity endorsement and its impact on purchase decisions. In this study, descriptive quantitative methods were employed. There were one hundred participants in the purposive sample method of data collection. Multiple linear regression analysis was performed using SPSS version 25 for data analysis. These results highlight the significant influence that celebrity endorsements have on consumers' decisions to buy MS Glow skin care products. The t-test carried out on the celebrity endorsement variable produces a value of 3.095 with a significance level of 0.003 below 0.05. This shows that the calculated t value exceeds the table t value. The brand image variable has a t value of 3.145 and a significance level of 0.002 which is below the limit of 0.05. The trust variable has a t value of 2.519 and a significance level of 0.013 which is below 0.05. In this regard, a conclusion can be drawn that positively and significantly the choice of purchasing MS Glow skin care products is influenced by brand image.